Jumlah Fi’liyah Learning Planning in the Quran Surah Luqman for Beginners - Azizah, Nurul; Alwani, Vielsa Ikna Azzahwa; Najwa, Ikmala; Arofatul B, Alfina; Hani, Wafro (AJIRSS: Asian Journal of Innovative Research in Social Science, 2023)
This research aims to determine the jumlah fi’liyah in Surah Luqman and determine the most appropriate learning plan for students at the initial level. This research uses a qualitative approach with a literature research type. Data analysis in this study used the Milles and Huberman technique. Based on the data analysis that has been carried out, the jumlah fi’liyah in surah Luqman is mentioned in each ayat in the form of a number consisting of fail isim dhomir and fail isim dhohir, so that short-term learning planning and grammar-tarjamah methods are appropriate to the learning process